The Influence of Economic Pressure, Social Capital, and Coping Strategies on Fishers's Family Well-being - Djakiman, Rapida; Sunarti, Euis; Krisnatuti, Diah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Fish families are vulnerable to poverty. The vulnerability of fishermen’s families leads to economic pressure that can reduce family well-being. This study aimed to analyze the influence of economic pressure, social capital, and coping strategies on the well-being of fishers. This cross-sectional study was conducted in the Aru Islands Regency, Maluku Province, Japan. The sample consisted of 50 skipper fisher families and 50 laborer families. Sampling was performed using snowball sampling. The data were processed using descriptive tests, independent sample t-tests, and structural equation modeling (SEM) tests. This research revealed that labor fisher families' economic pressures were higher than those of skipper fisher families. The social capital of skippers and laborers was classified as a low category. The coping strategies of the skipper and laborer fisher families were classified as in the moderate category. The well-being of skipper fisher families was higher than that of labor-fisher families. Economic pressure has a direct negative influence on fishers’ well-being. Social capital has a direct negative influence on fishers’ well-being. The research implication is that the well-being of a fisher's family can be increased by increasing social capital.